Thomas Tenant papers - Tenant, Thomas
Correspondence, accounts, surveys, and other legal papers relating to Thomas Tenant and the Bank of the United States, Baltimore, Md. Persons represented include Joseph J. Speed and Alexander Yearly.
In part, handwritten transcripts.
Banker.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Speed, Joseph J; Yearly, Alexander; Bank of the United States (Baltimore, Md.); Banks and banking -- Maryland -- Baltimore; Bankers